P12.05 Outreach chlamydia testing: upskilling a multidisciplinary workforce. (13th September 2015) - Tilley, DM; Dailey, BR; Sharp, NC; House, D
Abstract : Introduction: Chlamydia is the most common notifiable sexually transmitted infection (STI) in Australia, mostly affecting people aged 29 years and under. Offering testing in an outreach setting is an effective strategy for engaging young people and reducing the number of undiagnosed infections. Our service developed a model for Aboriginal Health Education Officers (HEOs) and Health Promotion Officers (HPOs) to offer urine chlamydia and gonorrhoea testing at community events. To enhance knowledge, confidence and skills, the Clinical Nurse Consultant and other specialist clinicians developed a comprehensive training package. The package includes an operations manual, lesson plan, presentation, role play scenarios, checklists, knowledge quiz and competency assessment. Topics include confidentiality, assessing risk and specimen collection procedures. Ongoing support from the clinical service is provided. Methods: Participants completed a pre and post training survey to measure knowledge and confidence in undertaking urine chlamydia and gonorrhoea testing in an outreach setting. The survey asked for responses to six statements on a scale of 1 (not at all) to 5 (completely). The average scores for each statement pre and post were calculated. Results: A total of nine staff completed the training between August 2014 and January 2015. The staff were from varying disciplines including Aboriginal HEO, HPOs, social work and student nursing. Eight pre and post surveys were completed. For all statements there was an increase in the average score in the post survey compared with the pre survey. The greatest differences were in the statements relating to assessing risk of harm in a young person and use of standard precautions. Conclusion: Participation in the comprehensive training demonstrated an increase in knowledge, confidence and skills of non-clinical health workers to undertake urine chlamydia and gonorrhoea testing in an outreach setting. The training is appropriate for staff from a variety of disciplines including Aboriginal HEOs, HPOs and social workers. Disclosure of interest statement: No disclosures of interest.